The Impact of Climate Change on Agricultural Risks Among Cotton Farmers in the Mutoko District of Zimbabwe - Mugambiwa S. Shingirai; Leonard Chitongo (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Scientists and policymakers are concerned about the effects of climate change on agricultural productivity and the well-being of farmers around the world. Alterations in the amount of precipitation and temperature have a direct influence on crop yields, although a rise in the prevalence of diseases and pests has a secondary but nevertheless important influence. The degree to which farmers believe climate change poses a threat to their agricultural operations is a decisive factor in determining whether or not they will make adjustments to their practices. This study assesses the impact of climate change on agricultural risks among cotton farmers in rural Zimbabwe. Thirteen (13) cotton farmers and employees of a company that buys and sells cotton were interviewed using a qualitative methodology. The study found that the cotton-growing industry has significantly incurred losses due to both the effects of climate change and the broader economic downturn. Several reasons related to Zimbabwe's economic collapse have contributed to the problem facing the nation's rural cotton farmers.